Social town planning - Greed, Clara, 1948- (Routledge, 1999)
Many issues such as access for the disabled, childcare facilities, environmental matters, and ethnic minority issues are excluded from town planning considerations by planning authorities. This book introduces the concept of `social town planning' to integrate planning policy and practices with the cultural and social issues of the people they are planning for. Part 1 provides background on the development of a social dimension to the predominantly physical, land use based, British town planning system. Part 2 investigates a representative selection of minority planning topics, in respect of g.